Kirk Patrick as a Calendar Debate training in Arabic for Students of the Center for the Promotion of Foreign Language - Arief, Gesbi Rizqan Rahman (JURNAL IJ-ATL, 2023)
This study aims to evaluate scientific debate training using the Kirkpatrick evaluation model, which is still rarely applied in the context of Arabic debate. Although the commonly used evaluation model is based on winning or losing in a competition, the Kirkpatrick model consisting of four stages—reaction, learning, behavior, and outcome—can provide in-depth insights to improve student competence. The research method used is a qualitative approach with a descriptive research type, and data were collected through interviews and documentation studies. The results showed that the Kirkpatrick evaluation model succeeded in providing a better understanding of improving student abilities, where in the reaction evaluation stage, students showed enthusiasm in sharing debate practice experiences; in the learning stage, there was an increase in ability before and after training; in the behavior stage, students were more receptive to input and suggestions from instructors; and in the outcome stage, students became more productive in Arabic debate competitions. The contribution of this study is to introduce the application of the Kirkpatrick model in Arabic scientific debate training as a tool to improve training effectiveness.